Membrane-based symmetric supercapacitors composed of cellulose solution-derived polydopamine-modified separators and polypyrrole/graphene-doped polydopamine-modified electrodes. (June 2022) - Xu, Daman; Heng, Yingqi; Qin, Xiang; Hu, Dongying
Abstract: In this study, using natural and renewable cellulose as substrates, the key materials for cellulose-based supercapacitors (polydopamine-modified separator: LIBR-PDA, composite membrane electrode: LIBR-PDA-GR/PPy-20) were successfully fabricated by using dopamine polymerization, phase inversion, graphene (GR)/polypyrrole (PPy) doping in LIBR/water system. The LIBR-PDA separator has a well-developed pore structure, providing channels for ion transport, and exhibits superior performance compared with commercial PP and TFC, such as lower internal resistance and higher ionic conductivity of the assembled supercapacitor. The LIBR-PDA-GR/PPy-20 electrode exhibits excellent electrochemical performance with an equivalent resistance of 1.3 Ω, specific capacitance of 336.1 F/g at 0.2 A/g. The membrane-based symmetric supercapacitor assembled from LIBR-PDA-GR/PPy-20 electrode and LIBR-PDA separator exhibits excellent electrochemical energy storage performance with a specific capacitance of 415.0 F/g at 0.2 A/g, energy density of 28.1 Wh/kg, corresponding to power density of 1.25 kW/kg at 1 A/g. It provides some insights for the development of cellulose membrane-based energy storage materials. Graphical abstract: Unlabelled Image Highlights: Polydopamine-modified cellulose separator constructed by phase inversion in LiBr/H2 O system Polypyrrole/graphene-doped polydopamine-modified electrodes through two-step method Designing material-complementary all-cellulose membrane-based symmetric supercapacitors This work sheds new light on cellulose-based electrochemical energy storage systems.